PENYELENGGARAAN IBADAH UMROH BERBASIS MASLAHAT - Firman Muhammad Arif (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2019)
This paper aims to explore the anomalies of organizing umrah worship, prove thetruth of information on abuse in conducting umrah worship and integrate(integration) istislah tools as maslahat-based instruments as a solution that is inline with Islamic values. The steps or methods taken by describing phenomena,facts and the reality of anomalies in organizing umrah, data on abuse. Varioussolutions are taken by the government with a preventive approach, modification of regulations, persuasive action to repressive. The reality of the fantastic number of victims in 2017 up to now requires the government to accelerate repairs by the system (devices, implementation principles) and by umrah caretaker (umrah organizers). The results of the writing indicate that istis (something that is valued and charged with maslahat) with various breakthroughs and updates that aredifferent from the previous ones, the number of victims of the Umrah congregation can be minimized or no longer worsen. The istislah concept is manifested in the form of regulation Minister of Religion Regulation No. 8 of 2018, limitation on the provision of minimum Umrah fees, fund collection from prospective pilgrims on the third party, provision of technology-based information systems, stipulation of repayment of Umrah fees no later than 3 months before departure, and coordination across institutions. Most of the “mischievous” umrah organizers were handled by convictions, refunds, opening a crisis center to revoking permits to minimize the increase in the number of victims. The misuse ofcongregation funds that are minimal from the realization of the departure of umrah or zero refunds is considered to have led other pilgrims to be more selective and vigilant and shift the paradigm of the Islamic community that cheap umrah irony will end in trouble.